Magnesium doped hydroxyapatite/sodium alginate biocomposite for bone implants application - Kanasan, Nanthini (2019)
Magnesium-doped Hydroxyapatite/Sodium alginate was successfully prepared by using precipitation method and this research was implement to enhance the physical, mechanical and biological properties of HA/SA. The properties of this materials are attributed to more cost-efficient, eco-friendly and maintaining the features required for bone implants application. This study reveals that, among the six composition ratios of HA/SA (100/0, 99.5/0.5, 97/3, 95/5, 92/8, and 90/10) implemented in this research, the 99.5/0.5 (HA/Sodium Alginate) sintered samples recorded the optimum results in terms of characterization of samples as determined through X-ray diffraction (XRD), Fourier Transform Infra-red (FTIR), Field Emission Scanning Electron Microscopy (FESEM), Energy Dispersive Spectroscopy (EDS) and Thermo Gravimetric Analysis (TGA). The 99.5/0.5 HA/SA are chosen and doped with various composition ratios of Mg-doped HA/SA from 0.5 wt.%, 1.0 wt.%, and 1.5 wt.% at 1000 to 1400 °C were investigated by evaluating the physical, mechanical, and bioactivity testing of the samples. The precipitation methods have been applied in this research due to its ability to produce high purity, low cost and produce more homogeneous prepared powders. The 1.0 wt.% of Mg-doped HA/SA prepared samples demonstrated better outcomes with the density and hardness around 2.90 g/cm3 and 4.11 GPa, respectively at 1300 °C. The decrease of the FTIR intensity peaks of PO43- ions is due to the increase of SA and Mg2+ ions. XRD analysis revealed that the decrease of peaks intensity are related with an increase of Na+ and Mg2+ content up to 1300 °C. FESEM analysis shows that the particles have an irregular and equiaxed shape. The best Mg concentration with sintering temperature at 1300°C is selected to be used in-vitro test of the immersed samples. From the observation, a noticeable precipitation of bone-like apatite on the surface of pure HA, HA/SA, and Mg-doped HA/SA was observed for 1 day, 7 days, and 14 days of immersion period. The in-vitro activity shows that the Mg-doped HA/SA induces more bone-like apatite formation on the surface of samples after 14 days the SBF immersion, compatible for the bone regeneration applications. In addition, the hardness of Mg-doped HA/SA of immersed samples recorded is 4.31 GPa. Based on the observed results, it can be suggested that the biocomposite can enhance the physical, mechanical, and bioactivity properties that offer promising future in bone implant applications.